Dual Mode: Establishing a Line-of-Sight Communication and Object Detection using Infrared Sensor Module - Aula, Abqori; Suryadi, Dedy; Islami, Jamhir (IPTEK The Journal of Engineering, 2024)
Miniature wheeled mobile robot is a very reliable and feasibly cheap material for robotic research. The cheap mobile robot can be repurposed for other task. This paper especially highlights the implementation of mobile robot for navigation. One of the purpose of navigation is to avoid collision. One of the most prevailing usage for object avoidance is infrared module. However, infrared signal can also be used for direct communication. In this paper, a dual mode function of infrared sensor module is presented. Using the same infrared module, communication and object detection are established. The proposed infrared module and switching algorithm are applied to a group of Arduino powered wheeled mobile robots. Preliminary lab-scaled tests show that the solution proposed in this paper perform well. Using an artificial experimental setup, the result shows that 19 out of 20 experiments (at 95% probability) were successful of detecting an object. The result also shows that 18 out of 20 simulations (at 90% probability) were able to successfully conduct a communication.